Curriculum Management Paud in Integrated Islamic Kindergarten Fania Salsabila Barokah Jambi - K. A. Rahman; Jemi Sihombing; Yuni Muriana Br Surbakti; Delpiyanita Br Karo; Bianda Dea Fadhilah (research, training and philanthropy institution Natural Aceh, 2023)
This study aims to find out how PAUD curriculum management in Fania Salsabila Barokah Jambi integrated Islamic kindergarten means management includes planning, implementing, organizing, supervising, and evaluating early childhood education curricula and knowing what problems are encountered in planning, implementing, organizing, supervision, and evaluation of early childhood education curricula. This type of research is descriptive and qualitative to obtain information related to curriculum management. The subjects in this study were school principals and teachers. Data collection techniques are by observing, interviewing, and documenting. Curriculum management is a set of plans and learning regarding objectives, content, learning materials, and the methods used as guidelines for learning activities. The curriculum is structured to realize educational goals that must be achieved and learning experiences that students must obtain. The curriculum applied in the Fania Salsabila Barokah Integrated Islamic Kindergarten, Jambi, is the 2013 curriculum, where education manages the 2013 curriculum by prioritizing needs and achieving goals in the vision, mission, and goals national policies that have been set. Curriculum management in Fania Salsabila Barokah Integrated Islamic Kindergarten, Jambi, includes planning, implementing, organizing, supervising, and evaluating the curriculum to ensure all learning activities can be carried out correctly and achieve the expected goals